ANALISIS ASIMETRI INFORMASI, SOSIALISASI SERTA UKURAN USAHA TERHADAP PEMAHAMAN USAHA MIKRO KECIL MENENGAH (UMKM) ATAS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTANBILITAS PUBLIK - Rio Rahmat Yusran; Yuliadi Yuliadi (Yayasan Akrab Pekanbaru, 2019)
Micro business, small and medium enterprises is part of public economy derived from community groups .Micro business, small and medium enterprises not progressing or cover business because the size of the capital must be fulfilled and large enough. Fenomena Micro business, small and medium enterprises because do not understand the procedure with the banking. In addition, the understanding of accounting standards are not enough by Micro business , small and medium enterprises. As for data analysis this study using multiple linear regression. In this study using descriptive quantitative methods, with the sample to technique purposive sampling. As 151 sample of Micro business , small and medium enterprises to the research. The results of the study is a partial ( test t ) asymmetry information, socialization, firm size significant of understanding accounting standard entity without public accountability With significant value0,00<0,05. The results of the study is a simultan ( test f ) asymmetry information, socialization and firm size significant of understanding accounting standard entity without public accountability With significant value0,00<0,05.